2022
DOI: 10.1002/adfm.202201541
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Coated Upconversion Nanoparticles for Sensitive Nucleic Acid FRET Biosensing

Abstract: Despite the significant advancements of developing upconversion nanoparticles (UCNPs) for high performance biosensing and bioimaging, the development of DNA‐functionalized UCNPs with thin coatings, efficient surface passivation, and fully functional DNAs for hybridization sensing in biological media remains extremely challenging. Here, a straightforward concept of labeling DNA to a thin polysulfonate polymer layer on UCNPs is presented. Both UCNPs and DNA preserve their full functionality as demonstrated by Fö… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…Therefore, the UCNP surface and Cy3.5 were in principle separated only by the thin PSS shell (∼2 nm) and the C 3 spacer (∼1 nm) . UCNPs prepared with those thin PSS shells and bioconjugated with DNA previously showed good stability without significant aggregation over up to 2 weeks and were successfully applied in DNA and RNA FRET assays. , The UCL kinetics (at 540 nm) of all DNA 1 -functionalized UCNPs (UCNP@PSS-DNA 1 ) were analyzed in HEPES buffer using both 980 and 808 nm excitation (Figure S7 and Table S3). Long 80 μs excitation pulses were used to reach intensity saturation and measure only the UCL decays of the different UCNPs, which were fitted with monoexponential functions (see Materials and Methods for details) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the UCNP surface and Cy3.5 were in principle separated only by the thin PSS shell (∼2 nm) and the C 3 spacer (∼1 nm) . UCNPs prepared with those thin PSS shells and bioconjugated with DNA previously showed good stability without significant aggregation over up to 2 weeks and were successfully applied in DNA and RNA FRET assays. , The UCL kinetics (at 540 nm) of all DNA 1 -functionalized UCNPs (UCNP@PSS-DNA 1 ) were analyzed in HEPES buffer using both 980 and 808 nm excitation (Figure S7 and Table S3). Long 80 μs excitation pulses were used to reach intensity saturation and measure only the UCL decays of the different UCNPs, which were fitted with monoexponential functions (see Materials and Methods for details) …”
Section: Resultsmentioning
confidence: 99%
“…The implementation of a model system as similar as possible to real-scenario FRET assays is a fundamental step to gain useful insights into the real working principles of such systems. For this reason, using a recently developed DNA-UCNP bioconjugation strategy for functional FRET assays, 9 we attached probe DNAs (DNA 1 ) on the UCNP surface. These probes were complementary to target DNAs labeled with Cyanine 3.5 dyes (DNA 2 -Cy3.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that our UCNPs were not optimized and that our assays were based on simple steadystate measurements without the necessity of time-resolved instrumentation, these very similar LODs are rather impressive and suggest that significantly lower concentrations may become quantifiable with optimized UCNP architectures and material compositions. 40 S6. In conclusion, thin PAA coatings (∼1 nm), direct attachment of DNA via EDC/sulfo-NHS chemistry, and close UCNP-dye distances resulted in the best UCNP-to-dye FRET DNA hybridization assay performance as demonstrated by sensitive quantification of miR-20a.…”
Section: T H Imentioning
confidence: 99%
“…Both Ln-doped NPs and DNA preserved their full functionality, as demonstrated by Förster resonance energy transfer hybridization assays with Cy3-conjugated complementary DNA. Ratiometric FRET from Ln-doped NP to Cy3 demonstrated that these nanohybrids are able to quantify miR20a in the 0.01-10 × 10 −9 M concentration range with a detection limit of 30 × 10 −12 M (4.5 fmol of miR20a) [90].…”
Section: Conclusion and Perspectivementioning
confidence: 99%